Clinical Significance of R202Q Alteration of MEFV Gene in Children With Familial Mediterranean Fever - Tufan ÇANKAYA,; Elçin BORA,; Meral TORUN BAYRAM,; Ayfer ÜLGENALP,; Salih KAVUKÇU,; Mehmet Atilla TÜRKMEN,; Alper SOYLU, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the clinical impact of the R202Q (c.605G>A) alteration of Mediterranean fever (MEFV) gene in children with familial Mediterranean fever (FMF). Patients and methods: Medical records of 115 patients (51 males, 64 females; mean age 6.6±3.8 years; range 8 months to 15.8 years) presenting with FMF pre-diagnosis were examined. Patients were classified into two groups based on number of mutated alleles (one-mutant allele and two mutant alleles), and these groups were classified into three subgroups (Group 1; subgroup 1: M694V/R202Q, subgroup 2: M694V/other, subgroup 3: other/other, and Group 2; subgroup 4: R202Q/-, subgroup 5: other/-, subgroup 6: -/-). Sex, age, abdominal pain, fever, arthritis or arthralgia, myalgia, erysipelas-like erythema, chest pain, amyloidosis, family history of FMF, and definitive FMF frequency were compared between groups. Results: The most common allele alterations were the heterozygous R202Q alteration (27%) and the compound heterozygous mutation M694V/ R202Q (20.9%). The R202Q alteration of MEFV gene was detected in 76 patients (66%) (15 homozygous). There was non-M694V (E148Q, V726A) mutation in two of these patients. One (50%) of the patients with isolated R202Q homozygous alteration and six (19%) of the patients with isolated R202Q heterozygous alteration had definitive FMF. In the two-mutant allele group; abdominal pain, fever, arthritis/arthralgia, and definitive FMF frequency were lower in subgroup 1 than subgroup 2. There was no significant difference in clinical findings and definitive FMF frequency between subgroup 2 and subgroup 3. In the one-mutant allele group, clinical findings did not differ between subgroups. Conclusion: R202Q alteration of the MEFV gene may lead to symptoms consistent with FMF. However, R202Q/M694V compound heterozygosity is more associated with mild phenotype than compound heterozygous mutation of M694V.